Oblique Deposited Ultra-Thin Silver Films on Polymer Gratings for Sensitive SERS Performance - Yi-Jun Jen; Meng-Jie Lin (Nanomaterials)
A small amount of silver was obliquely deposited onto a polymer subwavelength grating to form a metasurface that comprised silver split-tubes. An ultra-thin silver film with a monitor-controlled thickness of 20 nm at the corner of each ridge of the grating provided the most sensitive surface-enhanced Raman scattering (SERS) measurements. An excitation laser beam that was incident from the substrate provided similar or better SERS enhancement than did the general configuration with the laser beam incident directly on the surface of the nanostructure. Near-field simulations were conducted to model the localized electric field enhancement and to quantify the SERS performance, demonstrating the effectiveness of this novel deposition method.